2022
DOI: 10.1111/jfd.13623
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐protective efficacy of a live‐attenuated Edwardsiella ictaluri vaccine against heterologous Edwardsiella piscicida isolates in channel and channel × blue catfish hybrids

Abstract: Edwardsiella piscicida is a growing problem for catfish aquaculture in the southeastern United States, particularly in channel (Ictalurus punctatus) x blue (I. furcatus) catfish hybrids. Research has shown E. piscicida isolates recovered from farmed catfish in Mississippi form at least five discrete phyletic groups, with no apparent differences in virulence in channel and hybrid catfish. Laboratory trials have shown a live‐attenuated E. ictaluri vaccine (340X2) cross‐protects against at least one E. piscicida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…This study supports previous work demonstrating improved survival in fish following exposure to E. piscicida and subsequent challenge with E. ictaluri (Griffin et al, 2020a). These findings, coupled with reports of protection conferred by a live-attenuated E. ictaluri vaccine against E. piscicida infection in channel catfish (Griffin et al, 2020a;López-Porras et al, 2022) live-attenuated E. ictaluri vaccine exists , utilization of other Edwardsiella species in a combinatory fashion may optimize protection, especially in hybrids where vaccine efficacy may wane against high doses of E. piscicida (Griffin, Greenway, et al, 2020).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…This study supports previous work demonstrating improved survival in fish following exposure to E. piscicida and subsequent challenge with E. ictaluri (Griffin et al, 2020a). These findings, coupled with reports of protection conferred by a live-attenuated E. ictaluri vaccine against E. piscicida infection in channel catfish (Griffin et al, 2020a;López-Porras et al, 2022) live-attenuated E. ictaluri vaccine exists , utilization of other Edwardsiella species in a combinatory fashion may optimize protection, especially in hybrids where vaccine efficacy may wane against high doses of E. piscicida (Griffin, Greenway, et al, 2020).…”
Section: Discussionmentioning
confidence: 76%
“…Griffin et al (2020a) reported immersion in wild‐type E. piscicida produced 89%–100% relative percent survival in channel catfish exposed to E. ictaluri 35 days post‐immunization. López‐Porras et al (2022) reported similar protective effects afforded by heterologous E. piscicida isolates against E. ictaluri . While promising, results herein should be supported by more robust, replicated studies with larger sample sizes, particularly for blue catfish, which had the lowest survival in the initial challenges.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations